2007
DOI: 10.1002/jnr.21262
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine as an energy substrate in cultured neurons during glucose deprivation

Abstract: During glucose deprivation an increase in aspartate formation from glutamine has been observed in different brain preparations, including synaptosomes and cultured astrocytes. To what extent this reaction, which provides a substantial amount of energy, occurs in different types of neurons is unknown. The present study shows that (14)CO(2) formation from [U-(14)C]glutamine in cerebellar granule neurons, a glutamatergic preparation, increased by 60% during glucose deprivation, indicating enhanced aspartate forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…Glutamine consumption rates were also in the range of values reported for cerebellar neurons (Olstad et al,2007b) and increased significantly in cells subjected to hypoglycemia. Similar findings have been reported for primary cultures of cerebellar neurons together with a 60% increase in [ 14 CO 2 ] production measured during 1 hr of glucose deprivation in the presence of 0.2 mM [U‐ 14 C]glutamine (Peng et al,2007). The same study also demonstrated that, during hypoglycemia, glutamine was able to maintain a significant rate of oxygen consumption, confirming that glutamine oxidation is an important energy source for cerebellar neurons.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Glutamine consumption rates were also in the range of values reported for cerebellar neurons (Olstad et al,2007b) and increased significantly in cells subjected to hypoglycemia. Similar findings have been reported for primary cultures of cerebellar neurons together with a 60% increase in [ 14 CO 2 ] production measured during 1 hr of glucose deprivation in the presence of 0.2 mM [U‐ 14 C]glutamine (Peng et al,2007). The same study also demonstrated that, during hypoglycemia, glutamine was able to maintain a significant rate of oxygen consumption, confirming that glutamine oxidation is an important energy source for cerebellar neurons.…”
Section: Discussionsupporting
confidence: 86%
“…The values obtained for glutamine pools are much larger than those reported by Olstad et al (2007a; between 57 and 84 nmol/mg protein in the presence of 0.5 mM glutamine), probably because of the higher concentration of glutamine in the culture medium (2 mM). Glutamate pool sizes were much lower than those observed for glutamine but in the range of values previously reported for incubations in medium without glutamate (Olstad et al,2007b; Peng et al,2007).…”
Section: Resultscontrasting
confidence: 44%
“…Astrocytes metabolize glutamate to TCA cycle intermediates (Schousboe et al, 1993; Hertz and Zielke, 2004; Hertz et al, 2007), which diminishes the glutamate pool, and may drive astrocytic glucose consumption, ATP production and de novo glutamate synthesis (Hertz, 2011). Neurons also utilize glutamine and/or glutamate as energy substrates during glucose deprivation in vitro (Peng et al, 2007) or ischemia in vivo (Pascual et al, 1998). They similarly use glutamine or glutamate to replenish intermediates of the TCA cycle during metabolism of other substrates in vitro (Shokati et al, 2005).…”
Section: Astrocytes Control Cerebral Glutamate Levelsmentioning
confidence: 99%
“…During glucose deprivation, neurons turn to glutamine and glutamate for energy (48). Zaprinast does not affect glucose uptake or glycolysis (as assessed by lactate production), but its block of pyruvate transport mimics hypoglycemic conditions because less glucose-derived pyruvate is available to mitochondria.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 99%